IMPLEMENTATION OF PACKAGE C GROUP DISCUSSION LEARNING METHODS IN PKBM DEVELOPMENT OF CITIZENS, PANGKALAN DISTRICT, KARAWANG REGENCY - Diah Rodiah; Tika Santika; Ratna Sari Dewi (IKIP Siliwangi Bandung, 2023)
The aims of this study are to (1) describe the implementation process of the package C pursuit discussion learning method in PKBM Bina Warga, Pangkalan District, Karawang Regency; (2) Describe the supporting and inhibiting factors of the implementation of the package C pursuit discussion learning method at PKBM Bina Warga, Pangkalan District, Karawang Regency. In this study, the author uses a qualitative approach with a case study method. This research was conducted at PKBM Bina Warga, Pangkalan District, Karawang Regency. The subjects of this study consisted of: (1) the source of information consisted of three respondents, namely one manager of PKBM Bina Warga, and two tutors, (2) the source of the informant consisted of two learning residents. Determination of the subject using purposive sampling technique. Research data obtained through data collection techniques by observation, interviews and documentation studies. The research stages use the orientation stage, the exploration stage, and the member check stage. Data analysis was carried out using data reduction techniques, data presentation, and conclusion drawing. The results of the interviews obtained show that in the process of implementing group discussions there are steps that must be carried out, namely (1) determining the teaching materials to be discussed, (2) determining discussion groups and the number of participants in group discussions, (3) determining the time of discussion activities. groups, (4) reflection of each group from the results of the discussion, (5) conclude and explain the results of the discussion. Factors that can affect the learning process of group discussions are divided into 2, namely internal and external factors. Internal factors include interests, talents, awareness, interest and attention. Then external factors include tutors, the environment as well as the facilities and infrastructure available during the learning process.